TRANSFER PRAGMATIK DALAM KELUHAN PADA MAHASISWA ASING PEMBELAJAR BAHASA INDONESIA DI UGM - Riza Nuzulul Huda; B. R. Suryo Baskoro (Prasasti: Journal of Linguistics)
In the language competence that is inseparable from the speech act strategies, the socio-pragmatic transfer ability of second language learners can be explored in the use of speech acts which were currently examined through the use of complaints. This study aimed to describe what are the differences of speech act strategies in complaints used in English and Indonesian by International students and how pragmatic transfers in complaints are used by foreign students in producing languages. The data collection used Discourse Completion Test (DCT) with 4 International students in Fakultas Ilmu Budaya Universitas Gadjah Mada who stayed less than 6 months in Indonesia. The threat strategies were generally used to the hearer who have lower social status even with intimacy. However, when social status is aligned, the choice of complaint strategies switched to explicit strategies, on the other side, when the status of interlocutors is higher than the speaker, the use of the speech act strategy was replaced by implicit strategies.